2016
DOI: 10.1504/ejim.2016.073983
|View full text |Cite
|
Sign up to set email alerts
|

Global cities and liability of foreignness

Abstract: In recent years, more attention have been given to the sub-national determinants of multinational enterprises' location behaviour. However, the role of 'global cities' has received limited attention despite their central position in the global economy. In this thesis, I analyse and discuss the concepts of location, the liability of foreignness caused by MNEs' spatial separation of foreign operations, and their relation to the factors that drive MNEs toward, or away from, global cities. Rooted in the existing l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 50 publications
0
12
0
Order By: Relevance
“…Global cities are characterized by three distinctive features, including a high degree of global interconnectedness, the prevalence of a cosmopolitan environment, and the widespread availability of advanced producer services (Sassen, 2000(Sassen, , 2005, making them deeply connected and interlinked with each other despite a lack of geographic proximity (Sassen, 2005). Mehlsen and Wernicke (2016) state that locating activities in global cities rather than in peripheral areas is associated with a lower liability of foreignness, as a result of these distinct characteristics. This offers the potential for substantially lower investment costs and/or greater efficiency in developing and exploiting firm-specific advantages (FSAs) between different locations in the MNE network Verbeke, 2007, 2008).…”
Section: An International Business Perspective On Firm Strategiesmentioning
confidence: 99%
See 4 more Smart Citations
“…Global cities are characterized by three distinctive features, including a high degree of global interconnectedness, the prevalence of a cosmopolitan environment, and the widespread availability of advanced producer services (Sassen, 2000(Sassen, , 2005, making them deeply connected and interlinked with each other despite a lack of geographic proximity (Sassen, 2005). Mehlsen and Wernicke (2016) state that locating activities in global cities rather than in peripheral areas is associated with a lower liability of foreignness, as a result of these distinct characteristics. This offers the potential for substantially lower investment costs and/or greater efficiency in developing and exploiting firm-specific advantages (FSAs) between different locations in the MNE network Verbeke, 2007, 2008).…”
Section: An International Business Perspective On Firm Strategiesmentioning
confidence: 99%
“…Related to the international strategies of firms, the distinct characteristics of global cities have recently gained attention to explain their attractiveness for MNEs in their location strategies (Goerzen et al, 2013;Mehlsen and Wernicke, 2016). Goerzen et al (2013) found that 77% of MNEs locate activities outside their home market in global cities, which the authors attribute to a combination of firm-level and subsidiary-level factors related to corporate strategy, investment motives, and proprietary resources and capabilities.…”
Section: An International Business Perspective On Firm Strategiesmentioning
confidence: 99%
See 3 more Smart Citations